Psychometric properties of a modified version of Brazilian household food insecurity measurement scale - Pró-Saúde study - Marques,Emanuele Souza (2021)
Abstract We present results of initial steps of the psychometric evaluation of a proposed modified version of the Brazilian Household Food Insecurity Measurement Scale aimed at assessing adults’ recall of food insecurity at age 12. Data were obtained through self-administered questionnaires from civil servants at university campuses in Rio de Janeiro, who participated in the first and fourth waves of the longitudinal Pró-Saúde Study. We evaluated test-retest reliability (n=58), internal consistency, factor structure, convergent, discriminant validity (n=3,253). Test-retest reliability kappa coefficients were above 0.65; Cronbach’s α coefficient was 0.84. Factor loadings were above 0.800. The composite reliability was above 0.90. The square root values of the Average Variance Extracted were positive and statistically significant. Household food insecurity during childhood was strongly associated with larger family size and several sociodemographic conditions at age 12: female head of household, residence in rural area or small town, worse standard of living, and insufficient food due to lack of money. This initial evaluation suggests good performance. Further investigation should include additional psychometric properties and other population contexts.